Volume 2D: Turbomachinery 2014
DOI: 10.1115/gt2014-26931
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pressure Spectral Maps for Analysis of Influence of the Plenum Volume on the Surge in Centrifugal Blower

Abstract: *The influence of plenum volume on surge phenomenon in a centrifugal blower was studied by means of quasidynamic analysis. In this procedure, signals were gathered at 5 pressure tappings at 146 different positions of the throttling valve controlling the mass flow rate. Frequency spectra obtained by means of Fourier analysis are combined together in the form of colour maps with frequency as the abscissa and valve position as the ordinate. Such a map provides high-resolution information about spectral structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Earlier studies performed on the current machine and described e.g. by Liskiewicz et al 6 or by Kabalyk et al 5 suggested referring the appearance of this spectral pattern to inlet recirculation, the phenomenon typical to semi-open unshrouded impellers. 12 .…”
Section: Transient Measurementsmentioning
confidence: 85%
See 3 more Smart Citations
“…Earlier studies performed on the current machine and described e.g. by Liskiewicz et al 6 or by Kabalyk et al 5 suggested referring the appearance of this spectral pattern to inlet recirculation, the phenomenon typical to semi-open unshrouded impellers. 12 .…”
Section: Transient Measurementsmentioning
confidence: 85%
“…On the other hand, it is also known that if B mod;DP1:12 is decreased to 0.96 (by cutting the outlet pipeline), the pattern as in Figure 9 will not appear and no 12.7 Hz peaks will be noticeable on FFT spectra. 5 The above theses erect the following suggestions:…”
Section: Transient Measurementsmentioning
confidence: 98%
See 2 more Smart Citations
“…The recent development of high temperature energy storage systems could drive gas turbine cycles toward further layout modifications [9,10]. In all the mentioned cases, the gas turbine connection with such additional components generates a size increase for the volume located between the compressor outlet and the combustor inlet [11][12][13].…”
Section: Introductionmentioning
confidence: 99%